Electronic Structure of Monodithiolated IronOxotungsten Heterometallic Complexes: Integer‐Spin FeW Assembly. Issue 6 (15th April 2013) - Bose, Moumita; Moula, Golam; Sarkar, Sabyasachi
Abstract FeW heterometallic complexes, in which an FeX2 (X=Cl, SPh) moiety is attached to monodithiolene oxotungsten through a sulfide bridge, that is, [Ph4P]2[Cl2Fe(S)2WOS2] (1), [Ph4P]2[Cl2Fe(S)2WOS2(DMED)] (1, DMED=dimethylethylenedicarboxylate), [Ph4P]2[Cl2Fe(S)2WO(tdt)] (1, tdt=toluenedithiolate), [Ph4P]2[(SPh)2Fe(S)2WO(tdt)] (1), and [Ph4P]2[Cl2Fe(S)2WO(edt)] (1, edt=ethanedithiolate), are reported. Mössbauer and EPR spectroscopy, magnetism, electrochemistry, and electronic structural analysis based on DFT and TD‐DFT calculations show the transfer of electron from the iron center to the tungsten center, thus resulting in a ferromagnetically coupled FeIIIWV unit, along with antiferromagnetic intermolecular interactions, from the starting FeII and WVI compounds. A net spin of a S=3 ground state, which arises from ferromagnetically coupled FeIII and WV atoms, displays a rare X‐band EPR in normal mode at g≈7 in the solid state.